Revisão e valoração da antropoentomofagia - Sfeir, Vítor Cunha Gomes (2011)
Ethnoentomology is a branch of science that studies the interactions between humans and insects .Within this, it highlights the Anthropoentomophagy (the use of insects as human food), discussed in this paper through the review and analysis of scientific articles, monographs, reports, lectures and interviews of researchers from different parts of the world. The dissemination of research in this area seeks to change the misconception about insects in general (as evil and worthless), and value them as food resources capable a rational exploration with reduced environmental impact.